Modeling of the training preparation of highly qualified female hockey players - Shishkov, I. (Journal of Applied Sports Sciences, 2020)
The article is devoted to the study of effectiveness of building training and competitive loads of women`s national team of the Republic of Belarus for the European Indoor Hockey Championship (Indoor Hockey). The study was conducted at a separate, three-month stage of the annual training cycle.The Purpose of the study: To fi nd optimal ratio between training and competitive loads using block training system for highly qualified hockey players. To achieve the goal, the following tasks were set: 1. To determine the structure of training of Belarus national hockey players in clubs and during the training camps of the national team before the European Championship; 2. To evaluate training and competitive process as two separate areas of training for highly qualified hockey players; 3. To identify necessary volume and evaluate effectiveness of the use of nonspecific loads of anaerobic orientation in shock microcycles during training process of hockey players and final result. Research hypothesis: it was assumed that control and test games, as well as nonspecific loads of anaerobic orientation in shock microcycles, may have a positive effect on the efficiency of using block system for preparing highly qualified hockey players for a shortterm tournament. An analysis of the training structure of the women`s national team of the Republic of Belarus is presented from the perspective of the modern block system of periodization. Thus, it can be stated that the polycyclic principle of building the training process in Indoor hockey game sport is approved today. The obtained data on the structure of training of hockey players can be used as model characteristics.